2012
DOI: 10.1111/cmi.12080
|View full text |Cite
|
Sign up to set email alerts
|

Mouse cytomegalovirus egress protein pM50 interacts with cellular endophilin-A2

Abstract: SummaryThe herpesvirus replication cycle comprises maturation processes in the nucleus and cytoplasm of the infected cells. After their nuclear assembly viral capsids translocate via primary envelopment towards the cytoplasm. This event is mediated by the nuclear envelopment complex, which is composed by two conserved viral proteins belonging to the UL34 and UL31 protein families. Here, we generated recombinant viruses, which express affinity-tagged pM50 and/or pM53, the pUL34 and pUL31 homologues of the murin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 85 publications
1
29
1
Order By: Relevance
“…All herpesviruses analyzed so far utilize a core NEC of pUL50 -pUL53 homologs as a scaffold to assemble further NEC regulators and docking and adaptor proteins (7). However, a comparison between the findings of the present study on human CMV and a related study on murine CMV (54) revealed that the findings were only partly consistent. The central NEC components pUL50/pM50, pUL53/pM53, and p32/gC1qR were identified accordingly, but a huge number of NEC-associated proteins differed between the two systems.…”
Section: Differential Nec Assembly Comparing Human and Murinecontrasting
confidence: 55%
“…All herpesviruses analyzed so far utilize a core NEC of pUL50 -pUL53 homologs as a scaffold to assemble further NEC regulators and docking and adaptor proteins (7). However, a comparison between the findings of the present study on human CMV and a related study on murine CMV (54) revealed that the findings were only partly consistent. The central NEC components pUL50/pM50, pUL53/pM53, and p32/gC1qR were identified accordingly, but a huge number of NEC-associated proteins differed between the two systems.…”
Section: Differential Nec Assembly Comparing Human and Murinecontrasting
confidence: 55%
“…Various lines of experimental evidence suggested that the cytomegaloviral core NEC acts as a scaffold to assemble accessory NEC components (Muranyi et al, 2002;Milbradt et al, 2007Milbradt et al, , 2009Milbradt et al, , 2014Buchkovich et al, 2010;Lemnitzer et al, 2013). In particular, pUL50 defines the formation of the multimeric NEC by interacting with pUL53, PKCa, p32/gC1qR and emerin.…”
Section: Core Nec Formation Is Sensitive To Inhibitors Of Cdk Activitymentioning
confidence: 99%
“…Recently published proteomic data provided for the first time a candidate list of the associated viral and cellular constituents of the multimeric NEC for both HCMV and MCMV (15,18). For HCMV, at least four proteins were identified that directly interact with pUL50, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…As an essential step in HCMV replication, pUL50 and pUL53 heterodimerize and form the core of the NEC that serves as a scaffold for the recruitment of a group of viral and cellular NEC-associated proteins. The composition of the multimeric NEC of human and murine CMVs has recently been defined by proteomic analyses (15,18).…”
mentioning
confidence: 99%